Cloning and Expression of a Recombinant NS1 Antigen from a Dengue 3 Serotype Viral Isolate in Escherichia coli - Truong, Quoc Phong; Nguyen, Quang Anh; Nguyen, Thi Thu Thuy (JST: Engineering And Technology For Sustainable Development, 2022)
Dengue is dangerous infectious disease affecting on the more than half of the global population lives in areas risk of dengue. This disease is caused by infection with dengue virus (DENV) through the bite of infected female mosquitos. Detection of the dengue virus infection could be performed by virus isolation, molecular biology methods or by immunology methods. Non-structural protein 1 (NS1) has been considered as diagnostic marker for detection of dengue virus infection. In this study, the full length NS1 region from DENV serotype 3 was cloned in vectors to generate the recombinant constructs of pCR::DENV-3 ns1 and pET::DENV-3 ns1. rNS1 protein was successfully expression in E. coli BL21(DE3) and confirmed by Western blot. Optimal conditions for expression of rNS1 was established. The highest level of protein expression was achieved at induction conditions of 0.05 mM IPTG inducer, 2% ethanol, 37 oC for 4 hours. rNS1 protein was successfully purified by immobilized metal affinity chromatography. Obtained pure rNS1 could be used for further studies in the development of vaccine and diagnostic tools.